The Development Research and Application Prospect of Large Language Model Technology in The Financial Field - George. Gordon, Alex; Greece, Lucia; Richard (Journal of Computer Technology and Applied Mathematics, 2024)
With the continuous development and rapid progress of the information and computer age, large language model technology has been widely used in various fields and development operators, including, of course, the field of financial technology. In the financial field, large language model technology can promote the development and operation of finance from different angles, and make finance become a more intelligent new industry. Bring new development opportunities to finance. This paper focuses on the introduction of large language model, its development process in different development fields and stages, as well as its development principles and application status, and analyzes the development challenges and advantages of big language model in the application process in the financial field, and looks forward to the future development of big language model in the financial field.